MIGRATION FROM FACE-TO-FACE TO VIRTUAL CLASSES EVALUATION - Berg, Carlos Henrique (2022)
Digital learning is incorporated into educational spaces through constitutive elements such as technologies, active methodologies, educational strategies, and teacher training. The pandemic caused by Covid-19 forced higher education institutions to adapt to a new reality of social distancing, and with this, each component gained projection in that context. This study evaluated the migration and adaptation of educational content in the transition process from face-to-face to virtual learning. This article analyzes the media's point of view of the process. For this purpose, a qualitative study with a narrative-type methodological design was carried out based on the application of the evaluation in three subjects of graduate program. An ideal indicator for content adaptation was determined from the Glasser Pyramid. The objective was to check how close each subject is to an ideal distance learning model. As a relevant result, it was evidenced that the adaptation of educational content to the virtual environment, traditionally offered in person, was adequate.